Clinical outcome of image-guided adaptive radiotherapy in the treatment of lung cancer patients. (21st October 2015) - Tvilum, Marie; Khalil, Azza A.; Møller, Ditte S.; Hoffmann, Lone; Knap, Marianne M.
ABSTRACT: Background. Adaptive strategy with daily online tumour match is a treatment option when treating locally advanced lung cancer patients with curative intended radiotherapy (RT). Material and methods. Fifty-two consecutive lung cancer patients treated with soft tissue match, adaptive RT and small planning target volumes (PTV) margins were analysed. A control group of 52 consecutive patients treated with bone match, no adaptive strategy and larger margins was included. Patients were followed with computed tomography (CT) scans every third month. CT-images showing loco-regional recurrences were identified. The recurrence gross tumour volume was delineated and registered with the original radiation treatment plan to identify site of failure. All patients were toxicity-scored using CTCAE 4.03 grading scale. Data were analysed using the Kaplan-Meier analysis. Results. The median follow-up time was 16 months (3–35). Within a year, 35% of the patients in the adaptive group (ART-group) and 53% in the control group (No-ART-group) experienced loco-regional failure, showing improved loco-regional control in the ART group (p = 0.05). One patient in the ART-group and four patients in the No-ART-group showed marginal failure. Median overall progression-free survival time for the ART-group was 10 months (95% CI 8–12), and 8 months (95% CI 6–9) for the No-ART-group. Severe pneumonitis (grade 3–5) decreased from 22% in the No-ART-group to 18% in the ART-group (non-significant, p = 0.6). No significant difference in severe dysphagia was found between the two groups. Conclusion. In the first small cohort of patients investigated, implementation of soft-tissue tumour match and adaptive strategies for locally advanced lung cancer patients increased the loco-regional control rate without increasing treatment-related toxicity.